COVID-19 Disease and Ophthalmology: An Update (VITAE Academia Biomédica Digital, 2025)
The worldwide outbreak of the severe and acute respiratory coronavirus disease (COVID-19) caused by the coronavirus strain SARS-CoV-2 is currently the focal point of discussion due to the suffering this syndrome is causing to humanity. However, the ophthalmological implications of this syndrome has not yet been well described. Both eyes and tears as portals of entry and sources of contagion have been the subject of debate by many authors. The purpose of this review is to summarize the evidence currently available on COVID-19 and its ocular implications and manifestations, in both animals and humans, with the aim to facilitate prevention and educate the ophthalmological community on this subject. A review of the literature revealed that the results of some studies suggest that ocular symptoms commonly appear in patients with severe COVID-19 pneumonia and that it is possible to isolate the virus from the conjunctival sac of these patients. Conjunctivitis is not a common manifestation of the disease, but contact with infected eyes could be one route of transmission. Consequently, ophthalmologists need to have correct prevention strategies in place. Some guidelines regarding the prevention and management of ophthalmology clinics are reviewed. However, well-designed trials should be conducted to rule out other ocular manifestations that may result from COVID-19 infection and to understand the transmission.